2019
DOI: 10.1109/access.2019.2958955
|View full text |Cite
|
Sign up to set email alerts
|

Blind DOA Estimation in a Reverberant Environment Based on Hybrid Initialized Multichannel Deep 2-D Convolutional NMF With Feedback Mechanism

Abstract: The accuracy performance of traditional direction of arrival (DOA) estimation algorithms is seriously affected by the reverberation. Considering the advantage of the sparse characteristic of speech signal in time-frequency (T-F) domain, this paper presents a new blind DOA estimation method based on integrated deep learning and convolutional non-negative matrix factorization (NMF). Firstly, mathematic models of microphone array and room impulse response are built. In addition, we extracted blindly initializatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…As shown in Table 6, increasing the SNR from −5 dB to 5 dB in [51] reduces its RMSE from 0.08 to 0.02. Increasing the SNR from −5 dB to 5 dB in [53] reduces its RMSE from 3.3 to 0.3, while the RMSE drops from 1.3 to 0.28 when increasing the SNR from −10 dB to 10 dB in [43]. From the above relationship between SNR and RMSE, it can be seen that as the signal's SNR increases, the DOA estimation performance of the algorithm also improves.…”
Section: 2mentioning
confidence: 89%
See 3 more Smart Citations
“…As shown in Table 6, increasing the SNR from −5 dB to 5 dB in [51] reduces its RMSE from 0.08 to 0.02. Increasing the SNR from −5 dB to 5 dB in [53] reduces its RMSE from 3.3 to 0.3, while the RMSE drops from 1.3 to 0.28 when increasing the SNR from −10 dB to 10 dB in [43]. From the above relationship between SNR and RMSE, it can be seen that as the signal's SNR increases, the DOA estimation performance of the algorithm also improves.…”
Section: 2mentioning
confidence: 89%
“…Training and testing were performed using data sets of simulated and real environments, respectively, and performance evaluation showed that DOA estimation was improved even in noisy and reverberant environments. Fu et al [53] proposed a new blind DOA estimation method that uses the 2D convolution nonnegative matrix factorization method to generate a new array signal to estimate the azimuth angle of the reverberation signal. Wajid et al [55] proposed to use the recurrent neural network (RNN) model to learn some similar features used in DAS beamforming.…”
Section: Speech Doa Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Two methods exists to solve the uncertainty problem of frequency-domain method permutation: the first method is the geometric method based on the direction of arrival (DOA) [15]- [17], and the second method is the mutual parameter method that is based on the correlation between adjacent frequency points [18]- [21]. The DOA-based method considers the source signal and the spatial position of the sensor as prior knowledge.…”
Section: Introductionmentioning
confidence: 99%